Mechanical thrombectomy for acute multivessel occlusions with duplicated middle cerebral artery: A case report - Han, Hai-Ji; Sang, Qiang; Wang, Xi-Ming; Wu, Yan-Feng (Frontiers in Neurology, 2023)
Acute multivessel occlusions generally have multisite clot burden with lower successful reperfusion rates, and cerebrovascular anatomical variants increase the challenge of endovascular clot retrieval. We report a case of acute anterior multivessel occlusions patient with duplicated middle cerebral artery. Combined balloon guide catheter with stent retriever and aspiration approach has gained complete revascularization and good functional outcomes at 3 months follow-up.